ГРОМАДСЬКО-ПОЛІТИЧНА ДІЯЛЬНІСТЬ В. М. ЕЛЛАН-БЛАКИТНОГО: ДО ІСТОРІОГРАФІЇ ПИТАННЯ (Zaporizhzhia Historical Review, 2021)
In this article the author examines the historiography of a question of social and political activity of V.М. Ellana-Blakitnogo in the ХХ с. analyzes the existing literature and sources on this theme, investigates a few of the stages of the studies, which qualitatively are differed one from another in the methodological aspects. Based on this, the author comes to the conclusion that in connection with the specific historical circumstances and the ideological postulates, a study of social and political activity of V.М. Ellana-Blakitnogo and his role in the national motion appears insufficient to those studied.